2020
DOI: 10.3329/jbcbm.v5i2.44910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper and vermicompost on growth and yield of cowpea (Vigna unguiculata L.) Walp and nutrient accumulation in its fruits

Abstract: The effects of copper (Cu) and vermicompost (VC) on growth and yield of cowpea (Vigna unguiculata L.) Walp and nutrient accumulation in its fruits was examined. Eight treatments of Cu and VC were used. The highest plant height (226.67 cm), leaf number per plant (86.33), leaf area (174.12 cm2/plant), dry weight (13.98 g/plant), fruit length (52.4 cm), fruit number per plant (6), and fruit yield (5.65 g/plant) were recorded in Cu0.5 kg/ha + VC5 ton/ha treatment at harvest. The results of growth and yield of cowp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Therefore, our study supports previous findings that combination of bradyrhizobial strains and Streptomyces griseoflavus P4 increased N, P, and K uptakes of soybean and mung bean compared with un-inoculation treatment (El-Nahrawy and Omara 2017 and Htwe et al (2019). Additionally, Sharif et al (2019) found that the highest total macro and micronutrients (N, P, K, Zn, Cu, Mn and Fe) in cowpea seeds were achieved in organic treatment (vermicompost) compared to control treatments. Also, mixed application of biofertilizers and organic fertilizers can be enhanced the activity of phosphatase (acid and alkaline) around roots of Syrian cephalaria (Cephalaria syriaca L.), which led to increase the availability of N, P, Zn, Cu and Fe (Rahimi et al 2019).…”
Section: Seed Mineral Contentsupporting
confidence: 91%
“…Therefore, our study supports previous findings that combination of bradyrhizobial strains and Streptomyces griseoflavus P4 increased N, P, and K uptakes of soybean and mung bean compared with un-inoculation treatment (El-Nahrawy and Omara 2017 and Htwe et al (2019). Additionally, Sharif et al (2019) found that the highest total macro and micronutrients (N, P, K, Zn, Cu, Mn and Fe) in cowpea seeds were achieved in organic treatment (vermicompost) compared to control treatments. Also, mixed application of biofertilizers and organic fertilizers can be enhanced the activity of phosphatase (acid and alkaline) around roots of Syrian cephalaria (Cephalaria syriaca L.), which led to increase the availability of N, P, Zn, Cu and Fe (Rahimi et al 2019).…”
Section: Seed Mineral Contentsupporting
confidence: 91%
“…However, high doses of Cu inhibit the growth (Yagura et al 2019). In cowpea, Cu also increases the growth, yield, and nutrient uptake (Sharif et al 2019). Homeostatic amount of Cu increased the germination traits and growth in water melon plant (Liu et al 2016).…”
Section: Copper In Plant Growth and Developmentmentioning
confidence: 99%